Representasi Perempuan Pada Film Toxic (Analisis Semiotika Pada Film Toxic 2022) - Ika Rahmawati (Pusat Riset dan Inovasi Nasional, 2023)
Film is a form of mass communication that appeals to all demographics. According to a Jakpat survey, 88% of Indonesians like Korean films. Film is one of the communication media that has recently developed very rapidly. The film Toxic 2022 tells how the character Han Young Ju presents herself as a woman. This research is entitled Representation of Women in the Film Toxic 2002. What makes it interesting to examine how women are represented in the film Toxic 2022 is that it aims to find out how the character Han Young Ju presents herself as a woman. This study uses descriptive qualitative methods for semiotic research on the concept of Roland Barthes. The research takes and selects scene cuts that depict female figures and then analyzes the meanings contained, among others, connotative meanings, denotative meanings, and myths. The data collection technique is documentation and observation. The focus of the research is on action signs (scenes) that contain connotative meanings, denotative meanings, and myths contained in the film Toxic 2022. The research took seven scenes for analysis. The results obtained by this study show that the character Han Young represents a woman who is like life, that is, in the world of work, and can become a leader. The depiction of the figure of Han Young Ju, who experienced the world of work and became a leader, is explained in gestures, dialogues, actions, expressions, storylines, and shooting.